Analisa Pengaruh Parameter Line Width Terhadap Kekuatan Tarik Hasil Cetak Menggunakan 3D Printer - Sabri, Faris Ahmad Mizanus; Kamil, Syahiir; Sumawijaya; Bahri Widodo, Syamsul; Arif Adlie, Taufan; Arif, Zainal (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
3D printers of the extrusion type, also known as Fused Deposition Modelling (FDM), are widely used to create products from polymer materials in the desired shapes, such as bricks, holders, toys, and so on. The quality of the printed results is significantly influenced by the process parameters that can be adjusted. This study aims to analyze the effect of the line width parameter on the tensile strength of the prints produced using extrusion-type 3D printers. The specimen design follows the ASTM D638 type IV standard, with variations in the line-width printing parameters: 0.3 mm (P1), 0.4 mm (P2), and 0.5 mm (P3). The specimens were printed in PLA. Testing was conducted on 9 specimens, 3 for each line width parameter (P1, P2, P3), using a Universal Testing Machine. The average tensile strength values obtained were 27.97 MPa (P1), 31.61 MPa (P2), and 30.52 MPa (P3). The highest tensile strength was achieved with a line width of 0.4 mm. The results of the study indicate that the line width parameter affects the tensile strength of the printed results. Determining appropriate printing parameters can improve the quality of the printed product.